Safety and efficacy of PD-1 inhibitors plus tyrosine kinase inhibitors combination therapy in patients with advanced hepatocellular carcinoma combined with hyperbilirubinemia: a retrospective cohort study - Shida Pan; Shida Pan; Jianing Wang; Jianing Wang; Jiahe Tian; Jiahe Tian; Yilin Wang; Yilin Wang; Siyu Wang; Yingying Yu; Yingying Yu; Fengyi Li; et al. (Frontiers in Immunology)
BackgroundProgrammed death-1 (PD-1) inhibitors plus tyrosine kinase inhibitors (TKIs) combination therapy are considered as a first-line treatment recommendation for advanced hepatocellular carcinoma (HCC). However, patients with hyperbilirubinemia are excluded from this therapeutic option due to limitations in indications. There is a notable absence of published studies evaluating the safety and efficacy of the PD-1 inhibitors plus TKIs combination therapy in patients with HCC combined with hyperbilirubinemia.MethodsPatients with HCC complicated with hyperbilirubinemia who received combination therapy with PD-1 inhibitors and TKIs were retrospectively analyzed. Adverse events, tumor response, and laboratory parameters were recorded to assess the safety and efficacy of the treatment, as well as to identify potential risk factors influencing survival.ResultsA total of 108 participants were included in the study, with 56 patients (51.9%) reporting at least one adverse event, the majority of which were mild. The objective response rate (ORR) for the enrolled participants was 11.9%, and the disease control rate(DCR) reached 61.2%. The median overall survival (OS) for the entire cohort was 5.03 months, while the median progression-free survival (PFS) was 3.63 months. Multifactorial analysis showed that MELD score >18 and increased total bilirubin (TBIL) levels within one week were significant risk factors for OS. Patients with a decrease in TBIL levels within one week had significantly prolonged median OS (not reached vs 3.3months, P =0.013) and median PFS (7.03 months vs 2.77 months, P =0.010).ConclusionCombination therapy demonstrated favorable safety and tolerability among patients with HCC combined with hyperbilirubinemia. Patients who experienced a rapid decline in TBIL levels during the early phase of treatment with PD-1 inhibitors and TKIs were observed to derive clinical benefits. Early initiation of aggressive interventions aimed at reducing TBIL levels is recommended to optimize treatment outcomes.